THE STRUCTURE OF [P$(ReO,) (p-dppm),] [Re0,7,2 (Journal of Sciences, Islamic Republic of Iran)
Acluster[ pt (Reo )(?-dppm) ][Reo ],2 [dppm=ph Pch ] with oxidaton of [pt Re(CO) ](?-dppm) ][PF ] is prepred . Crystals are triclinic,pl; a= 14.154(4)?, b=14.213(3) ?,c = 20.522(4) ? , a = 78.938(14)?, ?= 75.812(19) ? , ?= 74,957(22) ? ;v = 3828.9(1 5) ? ,z =2 ; Eraf-Noniu CAD4 difhctorneter with Mo- K radiation, ? = 0.71073 ? ; R = 0.069, R = 0.077 for 284 parameters and 5414 reflections with I 3?(I).